The longitudinal impact of the COVID-19 pandemic on health behaviors, psychosocial factors, and cognitive functioning in older adults - Hausman, Hanna K.; Dai, Yunfeng; O’Shea, Andrew; Dominguez, Vanessa; Fillingim, Matthew; Calfee, Kristin; Carballo, Daniela; Hernandez, Cindy; Perryman, Sean; Kraft, Jessica N.; Evangelista, Nicole D.; Van Etten, Emily J.; et al. (Frontiers in Aging Neuroscience, 2022)
Older adults are at a greater risk for contracting and experiencing severe illness from COVID-19 and may be further impacted by pandemic-related precautions (e.g., social distancing and isolation in quarantine). The current study uses longitudinal data to examine changes in health behaviors, psychosocial factors, and cognitive functioning in a sample of 189 healthy older adults. The design assesses these changes during the pandemic compared to a pre-pandemic baseline and over the course of the pandemic in this at-risk population. Compared to their pre-pandemic baseline, during the pandemic, older adults reported worsened sleep quality, perceived physical health and functioning, mental health, slight increases in depression and apathy symptoms, reduced social engagement/perceived social support, but demonstrated better performance on objective cognitive tasks of attention and working memory. Throughout the course of the pandemic, these older adults reported continued worsening of perceived physical health and function, fewer depression symptoms, and they demonstrated improved cognitive performance. It is important to note that changes on self-report mood measures and cognitive performance were relatively small regarding clinical significance. Education largely served as a protective factor, such that greater years of education was generally associated with better outcomes across domains. Together, these findings may inform future study designs and intervention strategies to target areas of functioning negatively impacted in older adults by the COVID-19 pandemic.